The effects of a community-based walking program on walking ability and fall-related self-efficacy of chronic stroke patients - Lee, Jun-Min (J Exerc Rehabil, 2019)
The objectives of this study were to evaluate the effects of community-based walking training (CWT) on the walking ability and fall-related self-efficacy of chronic stroke patients and compare the effects of CWT to the conventional walking programs in stroke patients. Previous studies focused on walking speed, walking endurance, and balance. However, no studies have examined the changes in fall-related self-efficacy after CWT. In order to achieve purpose of this study, 45 chronic stroke patients, who were hospitalized at National Rehabilitation Center, were randomly divided into the CWT group (CWTG, n=15), the treadmill walking training group (TWTG, n=15), and the control group (CG, n=15). The treatment was conducted 3 times per week (30 min each) for 4 weeks. CWT was carried out by gradually increasing the difficulty level in various environments outside the hospital room. The results revealed that the CWTG was more effective in enhancing the walking ability and fall-related self-efficacy than the TWTG and the CG. These findings demonstrated that the CWTG increased the walking ability and fall-related self-efficacy of chronic stroke patients. Therefore, we suggest that adding CWT to standard rehabilitation might be an effective method for improving walking ability and fall-related self-efficacy in chronic stroke patients.